Comprehensive identification of microbial and metabolomic factors impacting ICC recurrence - Dang, Yuan; Xu, Shaohua; Huang, Jingyun; Peng, Xing; Yang, Yong; Wang, Yingchao; Yan, Yanan; Jiang, Fengle; Wang, Jianmin; Liu, Jingfeng (Frontiers in Oncology, 2026)
IntroductionIntrahepatic cholangiocarcinoma (ICC) originates from intrahepatic bile duct epithelial cells and its global incidence is rising. Surgery remains the primary treatment, but postoperative recurrence rates remain high.MethodsWe analyzed ICC patients' gut microbiota at four stages (preoperative, 7 days postoperative, 1 month postoperative, and during recurrence) using 16S rRNA sequencing and their serum metabolome via LC-MS/MS. Correlations among gut microbiota, metabolome, and clinical indicators were investigated, and candidate microorganisms and metabolites were integrated for multiomics clustering and staging.ResultsThis revealed significant increases in Bacteroides, Veillonella, and Enterococcus in ICC patients compared to healthy controls across all stages, suggesting these bacteria as potential markers of ICC progression. Microbial and metabolite changes were observed, with gut microbes influencing ICC development through kynurenic acid, linoleic acid, creatine, cholic acid, L-arginine, and the tumor microenvironment. Multiomics analysis showed that cholangiocarcinoma staging improves patient prognosis, particularly highlighting bile acids' role in type II hepatic phenotypes related to cholesterol metabolism.DiscussionOur study provides insights into ICC microbiome and metabolome associations with clinical features and survival.